Stable α‐FAPbI3 in Inverted Perovskite Solar Cells with Efficiency Exceeding 22% via a Self‐Passivation Strategy. (5th April 2022) - Zhang, Diwei; Zhang, Huidong; Guo, Huanxin; Ye, Fangyuan; Liu, Shuaijun; Wu, Yongzhen
Abstract: Formamidinium lead iodide (FAPbI3 ) has endowed power conversion efficiencies (PCEs) up to 25.5% in regular‐structured perovskite solar cells (PSCs) because of its optimal bandgap and enhanced thermal stability. However, the performance of FAPbI3 ‐based inverted‐structured PSCs is unsatisfactory. Herein, four kinds of commonly used hole transport materials (HTMs) are selected, including PEDOT:PSS, PTAA, NiO x, and MeO‐2PACz, to study their impact on the methylamine chloride (MACl)‐assisted one‐step deposition of FAPbI3 films. It is found that MeO‐2PACz is the optimal substrate for stabilizing black‐phase FAPbI3 and the corresponding inverted‐structured PSCs show the best photovoltaic performance. Nonetheless, the PCE is restricted by low open‐circuit voltage ( V OC ) due to non‐radiative recombination caused by MACl residues. Therefore, homologous PbI2 in situ passivation is implemented to passivate defects at grain boundaries. The addition of excess PbI2 in precursor solution remarkably decreases charge trap densities and elongates carrier lifetimes. As a result, the optimized device achieves an impressive PCE of 22.13%, which is the highest efficiency of FAPbI3 based on inverted‐structured PSCs. Moreover, the best device exhibits free hysteresis and excellent long‐term stability, maintaining 92% of the initial PCEs after 800 h aging under ambient conditions. Abstract : Homologous PbI2 in situ passivation strategy is demonstrated to passivate defect at grain boundaries of black‐phase FAPbI3 film via methylamine chloride‐assisted one‐step deposition. The excess PbI2 based self‐passivation on the FAPbI3 device not only enhances the power conversion efficiency from 14.87% to 22.13% but also leads to excellent durability in air, which is the highest PCE for FAPbI3 ‐based inverted PSCs reported to date.